Perempuan Korban Kekerasan Berbasis Gender Online dan Perlindungan Hukumnya - Kayus Kayowuan LewoLeba; Mulyadi; Yuliana Yuli Wahyuni (LPPM Universitas Ekasakti Padang, 2023)
Seeing from the historical side, violence is one of the oldest social problems, which may be as old as human civilization, this is understandable because basically humans are homo homini lupus creatures, referring to the thoughts of the famous philosopher Aristotle, that humans can become wolves for others, can become